Los servicios educativos y sanitarios en el desarrollo rural valenciano: principales problemas y posibles mejoras - Escribano Pizarro, Jaime (Geographicalia, 2014)
We examine, first, the main problems in operation of basic education and health-care services in rural areas to provide the local population efficiently; and second, the local population’s suggestions of how to solve these difficulties, improve the provision and quality of the services, and integrate their equipment into local development processes. Having based the investigation on a qualitative methodology (interviews) and focusing on the local key actors, the indicated problems and solutions are characterised by flexibility and multifunctionality. However, not all offered solutions can be applied simultaneously, since some of them require time to be developed.
Keywords: Educational services; health services; rural space; LEADER; Valencia.